국외 응급의료정보시스템 고찰을 통한 국내 시사점 - 김송이; Songyi Kim; 김경창; Kyoung Chang Kim; 김예지; Yeji Kim (HIRA Research, 2024)
Rapid and accurate exchange of medical information is essential for saving patients’ lives during medical emergencies. However, in Korea, a lack of data standardization, limited interoperability between systems, and restrictive data protection regulations significantly hinder the smooth sharing of information, posing a major challenge in emergency situations. The inability to access the patients’ prior medical records leads to treatment delays and adversely affects the quality of care provided. In contrast, countries such as the United States, the United Kingdom, and Singapore have established integrated data standards and real-time information-sharing systems to enhance the accessibility of emergency medical data. This study investigates the status of emergency medical information systems and access to information in the United Kingdom, France, Taiwan, Singapore, the Netherlands, Finland, the United States, Australia, and Sweden, aiming to find solutions that could promote emergency medical information sharing in Korea. The results of this analysis indicate that data standardization, the establishment of a centralized system, and the revision of laws regarding the use and sharing of emergency medical information are necessary to facilitate the exchange of medical data in emergency situations.